Study the Effect of Springboard on Concrete Performance Containing Low-Carbon Steel Spring - ghasem pachideh (Iranian Society of Structrual Engineering (ISSE), 2020)
One of the most important parameters in spring resistance and strength of concrete containing spring is its step length. In this paper, by adding a low-carbon steel spring with diameter, a number of steps and various mixing rates to self-compacting concrete, attempts have been made to improve its mechanical properties. For this purpose, springs of 8, 12 and 16 mm in diameter, 0.8 mm in thickness, with the number of steps of two, four and six in volumes of volumes of 0.2 and 0.4 in self-supporting concrete were added and compressive strength tests A cylindrical sample measuring 10 x 20 cm), tensile (a cylindrical sample measuring 10 x 20 cm) and a flexural beam (10 x 10 x 50 cm). The results indicate that using a 12 mm diameter spring compressive strength, the tensile and flexural strength of self-compacting concrete increased up to 29, 52 and 36%, but the use of a 16 mm diameter spring did not increase the mechanical properties of self-compacting concrete It also reduces. Due to the high stiffness and positioning of the 8 mm spring diameter within the size of the aggregate, the use of it to improve the mechanical properties of self-compacting concrete requires more research and recognition. Also, the main role in determining the strength of concrete containing springs is played by the diameter of the springs, and the number of step springs will not necessarily be a criterion for determining the increase or decrease of concrete strength. As a general conclusion, it can be argued that the use of six-step springs is not suitable, but the use of two- and four-step springs with regard to the percentage of use and the diameter of the spring used can increase the compressive strength, tensile and flexural strength Give.